A WiFi Link Budget Analysis of Drone-based Communication and IoT Ground Sensors - Jatupotn Supramongkonset; Sarun Duangsuwan; Sathapotn Promwong (My University, 2021)
An application of drone-based wireless networking in agricultural scenarios needs to analyze the radio link budget because of the uncertain propagation from the surrounding. This paper presents a link budget analysis between drone as a drone small cell (DSC) and Internet of Things (IoT) as a ground sensor. The measurement results show the received signal strength indicator (RSSI), path loss, and delay spread at 2.4 GHz frequency when considering the numbers of ground sensors to 15 points and use a single drone enabled with WiFi portable link. It can be found that drone DSC can compensate for the limited power of ground sensors and link budget analysis can optimally evaluate the communication channel in this scenario.
Keywords: UAV Applications and Optimization; Indoor and Outdoor Localization Technologies; Radio Wave Propagation Studies